Clinical severity of Clostridium difficile PCR ribotype 027: a case-case study. - Oliver W Morgan (Public Library of Science (PLoS), 2008)
Background Clostridium difficile is a leading infectious cause of health care associated diarrhoea. Several industrialised countries have reported increased C. difficile infections and outbreaks, which have been attributed to the emergent PCR ribotype 027 strain. Methods and findings We conducted a case-case study to compare severity of C. difficile disease for patients with 027 versus non-027 ribotypes. We retrospectively collected clinical information about 123/136 patients with C. difficile infections admitted to hospitals in the East of England region in 2006 and from whom stool isolates were cultured and ribotyped as part of an earlier national survey. We defined severe C. difficile disease as having one or more of shock, paralytic ileus, pseudo membranous colitis or toxic megacolon. Patient median age was 83 years old (range 3 to 98, interquartile range 75 to 89), 86% were prescribed antibiotics in the eight weeks before illness onset, 41% had ribotype 027 and 30-day all cause mortality during hospital admission was 21%. Severe disease occurred in 24% (95%CI 13% to 37%) and 17% (95%CI 9% to 27%) of patients with PCR ribotype 027 and non-027 ribotypes respectively. In a multivariable model, ribotype 027 was not associated with severe disease after adjusting for sex, discharge from hospital prior to 60 days of current admission, gastroenteritis on admission, number of initiator antibiotics for C. difficile disease, and hospital where the patient was admitted. Conclusions Our study found no evidence to support previous assertions that ribotype 027 is more virulent than other PCR ribotypes. This finding raises questions about the contribution of this strain to the recent increase in C. difficile disease throughout North America and Europe.